2010
DOI: 10.1002/dc.21454
|View full text |Cite
|
Sign up to set email alerts
|

Unusual clinical presentation of cutaneous malignant melanoma metastatic to the parotid gland; Initially discovered by fine needle aspiration: Case report and review of literature

Abstract: We report a case of malignant melanoma (MM) metastatic to the parotid gland, initially discovered on fine needle aspiration (FNA). The patient presented with a mass in the parotid gland area with previous history only significant for prostatic carcinoma. The initial FNA impression was melanoma. The smears were hypercellular with bloody necrotic background. The cells were epithelioid with mild nuclear atypia. Discrete cytoplasmic pigmentation was seen. No lymphoglandular bodies were noticed. Fragments of benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…More than 75% of parotid metastases are believed to spread into the intraparotid lymph nodes of a nearby malignancy. The parotid gland is known to function as a filtering center for lymphatic drainage in the head and neck region [ 7 ]. Some studies have reported facial melanomas with metastasis to the parotis and ipsilateral levels I–IV [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than 75% of parotid metastases are believed to spread into the intraparotid lymph nodes of a nearby malignancy. The parotid gland is known to function as a filtering center for lymphatic drainage in the head and neck region [ 7 ]. Some studies have reported facial melanomas with metastasis to the parotis and ipsilateral levels I–IV [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although regional and distant metastatic disease should always be considered, it is well-known that, for the parotid gland, around 80% of metastases are derived from squamous cell carcinomas (SCC) of the head and neck region, followed by cutaneous carcinomas and mucosal melanomas. [4][5][6][7][8] Of note, metastatic carcinomas from the breast, lung, kidney and prostate have also been reported in the parotid gland. [4][5][6][7][8] The submandibular gland is more commonly a site of metastases from these latter distant sites.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Of note, metastatic carcinomas from the breast, lung, kidney and prostate have also been reported in the parotid gland. [4][5][6][7][8] The submandibular gland is more commonly a site of metastases from these latter distant sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various hematopoietic and lymphoid malignancies, including lymphomas, constitute a significant portion of SMSGs, with a reported incidence of up to one‐third of all SMSGs . Metastatic carcinomas from sites in the breast, lung, kidney, thyroid, liver, and stomach have also been reported in several small case series and in single‐case reports of SMSG …”
Section: Introductionmentioning
confidence: 99%